Aplikasi Sistem Pencarian Sukarelawan Menggunakan Metode Simple Additive Weighting (SAW) Pada Kementerian Kesehatan RI Berbasis Mobile - Devie Alifa Paramitha; Muhammad Farhan Ilhamdi; Muhammad Farhan; Fajar Masya (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
With a rapid growth in technology nowadays, helping information dissemination. But, in affect of covid-19 pandemic resulting in the lack of place for skill development for the next generation. Volunteering is one of the popular social activites in Indonesia. As such, the information dissemination about the social activities just limited on “mouth to mouth”. Therefore, Re-L1 designed to spread information easily from event holders to volunteers. In this case, especially for Indonesian Ministry of Health. This application is based on android for the volunteer to register. Also, the business process is analyzed using PIECES methodology and is designed using Rapid Application Development (RAD) methodology. This application also supported with decision support system methodology, Simple Additive Weighting (SAW) in order to produce an optimal volunteer and fit the requirement that Ministry of Health needs. This research resulting an application that helping Ministy of Health on opening a volunteer reqruitment for the social activities.